2008
DOI: 10.1088/0953-8984/20/16/165206
|View full text |Cite
|
Sign up to set email alerts
|

Rare-earth site distributions in R(PO3)3(R = La,Nd,Er,Yb) metaphosphate glasses by reverse Monte Carlo simulations

Abstract: The R−R pair distribution functions of rare-earth metaphosphate glasses R(PO 3 ) 3 with R = La, Nd, Er, Yb are determined from total X-ray and neutron scattering data by the Reverse Monte Carlo method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The observations were verified by molecular dynamics simulations [37]. Reverse Monte Carlo (RMC) based on X-ray and neutron diffraction data show the decrease of the fraction of short R-R distances for RP 3 O 9 glasses with R = La, Nd, Er, Yb, with decreasing R 3+ ion size [38]. The RMC pair correlations of the ErP 3 O 9 glass [38] broadly agree with those of the TbP 3 O 9 glass [36,37].…”
Section: Model Conception For the Behavior Of N Romentioning
confidence: 68%
See 1 more Smart Citation
“…The observations were verified by molecular dynamics simulations [37]. Reverse Monte Carlo (RMC) based on X-ray and neutron diffraction data show the decrease of the fraction of short R-R distances for RP 3 O 9 glasses with R = La, Nd, Er, Yb, with decreasing R 3+ ion size [38]. The RMC pair correlations of the ErP 3 O 9 glass [38] broadly agree with those of the TbP 3 O 9 glass [36,37].…”
Section: Model Conception For the Behavior Of N Romentioning
confidence: 68%
“…Reverse Monte Carlo (RMC) based on X-ray and neutron diffraction data show the decrease of the fraction of short R-R distances for RP 3 O 9 glasses with R = La, Nd, Er, Yb, with decreasing R 3+ ion size [38]. The RMC pair correlations of the ErP 3 O 9 glass [38] broadly agree with those of the TbP 3 O 9 glass [36,37]. Diffraction experiments which would show the predicted lack of short R-R distances for ultraphosphate glasses of x =~0.16 are difficult due to the small R 2 O 3 fractions and, thus, small weight of the R-R correlations.…”
Section: Model Conception For the Behavior Of N Romentioning
confidence: 99%
“…The FSDP is frequently considered to be indicative of structural correlations over medium range length scales. For example, the FSDP in rare earth metaphosphate glasses is associated with rare earth-rare earth correlations [28]. The present RMC model enables us to examine the contribution to i (Q) from different interatomic correlations.…”
Section: Discussionmentioning
confidence: 99%
“…MD modelling of phosphate glass has been very limited, being reported only for Li [17], Na [18], Mg, Zn and Pb [19], and Tb [20] metaphosphate glasses. RMC modelling has been more common, being reported for Zn, Sr, Ba, Na and K [21], Li [22], Mg and Co [23], K [24], Zn [25][26][27] and lanthanides [28,29]. There has only been one reported model for Ca metaphosphate glass in 1987, [21], being a preliminary RMC study which used only x-ray diffraction data.…”
Section: Introductionmentioning
confidence: 99%
“…The previous MD study of Tb metaphosphate glass showed an R • • • R correlation with a small peak around 3.9 Å with nTb Tb = 0.9 and a larger peak around 6.1 Å with nTb Tb = 7.7 [24]. Recent work by Hoppe using reverse Monte Carlo modelling of Er meta-phosphate glass [30] also showed an R • • • R correlation with main feature at 6.2 Å having nR R = 7.14 and a second smaller feature at 4.3 Å having nR R = 0.8.…”
Section: Discussionmentioning
confidence: 95%